The question international legal regime security research and outer space for peaceful purposes - Стельмах, Ольга Станіславівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2009)
This article addresses the issue of providing the international legal regime for security of exploration and uses ofouter space as a comprehensive phenomenon, presents the author's concept for building of global collective spacesecurity system by means of implementation of the international law mechanisms and principles.